Eristik I. - Ringelnatz, Joachim; Schwiede, Eva-Maria (Köln : Köln Salon, 1997)
Baur, Marlene ; Gagel, Reinhard ; Höptner, Axel ; Kaiser, Lisa ; Koch, Hans W. ; Kochems, Stefan ; MiegL ; Mundt, Reinhart ; Neumann, Daniel ; Pieroni, Andrea ; Schmidt Dzionsko, Maria ; Tsortanidis, Andreas ; Wagner, Andreas
Duits
Eristik I, Accrochage des Köln Salons, Köln, 23.11. - 22.12.1997
boek